Comparative analysis of morphological and farmers' cognitive diversity in yams landraces (Dioscorea spp.) from southern Ethiopia - Tamiru, M.; Becker, H.C.; Maass, Brigitte L. (2011)
Neglected by research and development, knowledge of the genetic diversity in Ethiopian yams is found mainly with the local farmers. The local yam classification system in Southern Ethiopia was studied through individual and key informant interviews. Data collected include attributes/traits of each landrace used in the folk taxonomy. Local farmers recognize two major categories of yams: ‘hatuma boye’ (‘male’ yam) and ‘macha boye’ (‘female’ yam). This categorization has no reference to the reproductive biology of the plant. “Female” yams mature early and produce tubers of excellent quality, but are less vigorous in growth compared to ‘male’ yams and yield poorly under sub-optimal conditions. Whereas, ‘male’ yams mature late, grow vigorously and are tolerant to drought. Individual landraces are further identified based on variations in maturity time, morphological and/or growth attributes. Eighty-two yam accessions collected from Gedeo, Sidama, Wolayita and Gamo-Gofa zones were characterized using 42 qualitative morphological variables. Cluster and principal component analyses gave seven distinct groups, revealing that the overall structure of morphological diversity is consistent with farmers’ classification. Nevertheless, no clear morphological variations were observed between some differently named landraces. Few landraces known by the same vernacular name were also morphologically distinct. This study demonstrated the existence of a well-defined local classification system and a wide variability among the accessions studied. It also revealed the need for detailed phylogenetic studies to determine the species identity of the accessions studied and broaden the knowledge base of Ethiopian yams.